2023
DOI: 10.1002/sus2.132
|View full text |Cite
|
Sign up to set email alerts
|

CoSe2 supported single Pt site catalysts for hydrogen peroxide generation via two‐electron oxygen reduction

Abstract: Electrocatalytic oxygen reduction reaction (ORR) to prepare H 2 O 2 in acidic medium has the advantages of green, safety, and portability, which shows broad development prospects. However, it still suffers from low catalyst activity, insufficient selectivity, and high cost. Herein, Pt 1 /CoSe 2 with ultralow 0.01 wt.% Pt atomic distribution was synthesized by a simple hydrothermal method. The Pt 1 /CoSe 2 with ultralow Pt content exhibits high activity, high selectivity, and long-term stability for ORR to H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…As revealed in Figure 2k; and Figure S10, and Table S2, Supporting Information, the primary peak signals of Co 2p are recognized as Co 2+ and Co 3+ , respectively. [43][44][45] Concurrently, the Co 2+ /Co 3+ intensity ratio in Ir@Co 3 O 4 (S) is 0.466, which is much smaller than pristine Co 3 O 4 (0.940). Taken together, we deduce that there are distinct, robust interactions and substantial electron transfer between Ir clusters and Co 3 O 4 , thereby enabling the stable anchor of Ir clusters.…”
Section: Resultsmentioning
confidence: 99%
“…As revealed in Figure 2k; and Figure S10, and Table S2, Supporting Information, the primary peak signals of Co 2p are recognized as Co 2+ and Co 3+ , respectively. [43][44][45] Concurrently, the Co 2+ /Co 3+ intensity ratio in Ir@Co 3 O 4 (S) is 0.466, which is much smaller than pristine Co 3 O 4 (0.940). Taken together, we deduce that there are distinct, robust interactions and substantial electron transfer between Ir clusters and Co 3 O 4 , thereby enabling the stable anchor of Ir clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen evolution reaction (HER) as a half-reaction of water splitting has made great progress in the design of catalysts and the understanding of catalytic active sites in recent years. In particular, Pt catalysts exhibit high-efficiency HER performance, but the high cost and scarcity of noble metals severely limit their applications. Single-atom and cluster catalysts have attracted increasing attention due to their high atomic utilization and high intrinsic activity. Lu et al found that the isolated Pt atoms on graphdiyne have high HER activity due to the high total unoccupied density of states of Pt 5d orbitals and close to zero of Gibbs free energy of the hydrogen adsorption . Wang et al reported a Pt single-atom anchoring on layered double hydroxide (LDH), where the interlayer Pt single-atom vastly enhanced the electron transferability of LDH support, providing high HER performance .…”
Section: Introductionmentioning
confidence: 99%